Tissue Damage and Inflammation Induced by Snake Venoms - Lomonte, Bruno (2014)
Tesis Doctoral, Universidad de Goteborg, Suecia, 1994. También disponible en: http://brunolomonte.comli.com/1994_PhD_Thesis_alone.pdf